Cuerpo, Sonido y Neurociencias - Rodríguez Kees, Damián (Universidad Nacional del Litoral, 2020)
Although the incorporation of the gaze on the gestural aspects that lead to the production of sound on stage in music of the twentieth and twenty-first century is not frequent, there is already a theoretical corpus that enables analysis and new reflections on the fundamental participation of the gesture in the configuration of the musical fact. This work tries to broaden this view, developing a contribution to the mentioned corpus, presenting some conclusions to an investigation on the relationship between sound and the gesture that produces it on stage. Thus, we carry out an analytical approach to recent works belonging to the field of the so-called «contemporary musical theater", resorting, from a phenomenological perspective, to new contributions from the neurosciences and to a revisit of the already centennial category of kinestesia.